Tasawuf Sunda dalam Naskah Asmarandana Ngagurit Kaburu Burit (OR. 7876) - Jajang A. Rohmana (Ulumuna, 2013)
The spread of Islam in the Archipelago was closely tied to the roles of Sufi ulama. The circulation of Sufi work in Nusantara proves a strong connection between this region and the Middle East. In West Java, a number of these work expose Sufi teachings in the form of Sundanese Sufi literature, such as the work by Haji Hasan Mustafa. He is considered the greatest Sundanese poet whose work features strong influences of wahdat al-wujud. This paper aims to examine Sundanese Sufism expressed in Mustafa’s work of Asmarandana Ngagurit Kaburu Burit. This study shows that this work contains Sufi’s path that explores the self and its encounters with Supreme Being and the self’s diffusion, where there is no longer existence except the One. Mustafa called his Sufi poetry imperfect suluk because it was written in late afternoon. His work reveals local Sufi accommodation to wah}dat al-wujud in Sundanese language and culture.